Accidental cisplatin overdose in a child: Successful management with repetitive plasmapheresis and use of chemoprotective agents - Emir, Suna; Özyörük, Derya; Arman, Özlem; Özbek, Namık; Tunç, Bahattin (The Turkish Journal of Pediatrics, 2016)
Cisplatin is one of the effective chemotherapeutic agents widely used for many tumor types in children. The most serious complications of cisplatin overdose are nephrotoxicity and ototoxicity. It may lead to life-threatening complications and even death. We report a 13-year-old female patient with osteosarcoma who received a massive cisplatin overdose mistakenly. She was given cisplatin 120 mg/m2/day for consecutive two days, instead of one day (total 240 mg/m2) due to a prescription error. After 12 hours, her cisplatin level was measured as 8,500 ng/ml (normal: 1,000-5,000 ng/ml). She was treated with repeated plasmapheresis combined with use of two chemoprotectants, (N-acetylcysteine and amifostine). On her follow up, renal functions and audiometric tests remained normal. According to our experience with our case, early urgent combined treatment is very important in the management of cisplatin overdose.